The vowel /a/ as the main portal to humanity’s language and culture faculties - Puppel, Stanisław (Lingua Posnaniensis, 2023)
The vowel /a/ is regarded here as the initial sound, based on earlier vowel-like vocalization in humans, especially the neonate cry. This particular type of vocalization marks the true beginning of human language in the ontological perspective. Its presence is absolutely fundamental for the generation and maintenance of oxygen-based language and culture complex. All of human life is conducted in the human auditive world of organization based on the air (the aerial condition).